Study of volume fractions on biphasic stratified regime using gamma ray - William Luna Salgado; Luis Eduardo Barreira Brandão (Brazilian Journal of Radiation Sciences)
In the oil industries, interconnected pipelines are used to carry large quantities of petroleum and its byproducts. This modal has an advantage because they are more economical, eliminate a need for stocks and, in addition, great safety in operation minimizing a possibility of loss or theft when transported another way. In many cases, especially in the petrochemical industry, the same pipeline is used to carry more than one type of product. They are called poliduct. In the operation of a poliduct there is a sequence of products to be transported and during the exchange of the product, there are still fractions of the previous product and this generates contaminations. It is therefore important to identify precisely this region in order to reduce the costs of reprocessing and treatment of discarded products. In this way, this work presents a methodology to evaluate the sensitivity of the gamma densitometry technique in a study of the calculation of volume fractions in biphasic systems, submitted to the stratified flow regime. Using computational simulations using the Monte Carlo Method with the MCNP-X code, measurement geometry was proposed that presented a higher sensitivity for the calculation of volume fractions. The relevant technical data to perform a simulation of the scintillator detectors were based on information obtained from the gammagraphy technique. The study had a theoretical validation through analytical equations, and the results show that it is possible to identify volume fractions equivalent to 3%.